5th Symposium on Terrestrial Gravimetry: Static and Mobile Measurements (TG-SMM 2019) Proceedings of the Symposium in Saint Petersburg, Russia, October 1 - 4, 2019 - Freymueller, Jeffrey T.; Sánchez, Laura (International Association of Geodesy Symposia, 2023)
This open access volume contains the proceedings of the 5th Symposium on Terrestrial Gravimetry: Static and Mobile Measurements (TG-SMM2019) held in St. Petersburg, Russia, October 1 - 4, 2019. The symposium was hosted by the State Research Center of the Russian Federation Concern CSRI Elektropribor, JSC and was attended by 75 participants from 15 different countries. 32 oral and 20 poster contributions were presented in four different topical sessions: Terrestrial, shipboard and airborne gravimetry, Absolute gravimetry, Relative gravimetry, gravity networks and applications of gravimetry and Cold atom and superconducting gravimeters, gravitational experiments.